The Effect of Leverage, Capital Intensity and Deferred Tax Expense on Tax Avoidance - Cicik Suciarti; Elly Suryani; Kurnia Kurnia (Journal of Accounting Auditing and Business, 2020)
This research was conducted to determine the simultaneous and partial effect of Leverage, Capital Intensity and Deferred Tax Expense on Tax Avoidance in the automotive subsector companies listed on the Indonesia Stock Exchange (IDX) during 2012-2018. The sampling technique used was purposive sampling. The method of data analysis uses panel data regression analysis using Eviews 10 software by conducting several stages of testing. The results of this study indicate that leverage, capital intensity, and deferred tax expense simultaneously significantly affect tax avoidance. Capital intensity partially has a significant effect on tax avoidance in a negative direction. Meanwhile, leverage and deferred tax expense partially have no significant effect on tax avoidance.